PEMANFAATAN STRATEGI MULTIMODAL DALAM PEMBELAJARAN BAHASA INGGRIS: STUDI KASUS DI FKIP UM SUMATERA BARAT - Mezia Kemala Sari; Fadila Rasyida (Politeknik Negeri Jakarta, 2025)
The swift advancement of digital technology has revolutionized language instruction, necessitating creative methods to improve student interest and competency. The purpose of this study is to evaluate how well the multimodal approach to teaching English to undergraduate students at FKIP Universitas Muhammadiyah Sumatera Barat works. Using a qualitative descriptive approach, information was gathered by means of semi-structured interviews, classroom observations, and examination of 20 participants' multimodal projects. The results show that by combining textual, visual, and aural modalities, the multimodal approach greatly enhances students' speaking, writing, listening, and reading abilities. The method also improves student motivation and cultivates multiliteracy abilities, which are critical for communication in the digital age. Nevertheless, issues including the lack of adequate technology and the requirement for teacher preparation were noted. The study highlights practical implications for educators and curriculum developers to incorporate multimodal strategies systematically to optimize language learning in digital contexts.